Unrealized Potential : The High Cost of Gender Inequality in Earnings - Wodon, Quentin T.; de la Brière, Bénédicte (Washington, DC: World Bank, 2018)
This first note in the series on the cost of gender inequality focuses on the losses in national wealth due to gender inequality in earnings. There is a substantial literature on the impact of gender inequality on economic growth and performance. By focusing on wealth, the approach usedfor measurement in this note is different. Wealth is the assets base that enables countries to produce income Gross Domestic Product or GDP). A country’s wealth includes various types of capital. Produced capital comes from investments in assets such as factories, equipment, or infrastructure. Natural capital includes assets such as agricultural land and other renewable and non-renewable natural resources. However, the largest component of countries’ wealth typically resides in their people. As noted in the recent World Bank study on the Changing Wealth of Nations, human capital measured as the present value of the future earnings of the labor force accounts for two thirds of global wealth. If gender equality in earnings were achieved, countries could increase their human capital wealth, and thereby their total wealth substantially. This would enable them to strengthen the sustainability of their development path. Gender inequality has major economic implications forwomen, communities, and countries in a range of areas. While the cost of gender inequality – in terms of human capital losses - for development is not solely due to losses in earnings, the impact of gender inequality on earnings is key. This is the area on which this note focuses.